CATACLASTIC SOLUTION CREEP OF VERY SOLUBLE BRITTLE SALT AS A ROCK ANALOGUE - den Brok B.; Zahid M.; Passchier C. (My University, 1998)
Until about the late 1960s, macroscopically ductile deformation of quartz was seen as a microscopically cataclastic process by most geologists (cf. the origin of the name `mylonite'). Undulatory extinction, subgrains, recrystallised grains and even crystallographic preferred orientations were interpreted as due to water-assisted brittle deformation processes. Nowadays, by contrast, the occurrence of these optical microstructures is considered as conclusive and unequivocal evidence for dislocation creep. The abundance of these microstructures in naturally deformed rocks lead to the conclusion that dislocation creep is the most important ductile deformation mechanism within the Earth's crust. We studied whether a water-assisted brittle deformation mechanism could, in principle, be able to produce apparent `crystal plastic' microstructures, and how. To this end we performed a long-term deformation experiment using soluble brittle salt (NaClO3) as an analogue for quartz. A single crystal of NaClO3 was uniaxially stressed for 44 days at room temperature in the presence of a saturated NaClO3 solution under atmospheric pressure. The crystal was microscopically studied during the experiment. It slowly deformed by cataclastic creep. First, irregular free face dissolution structures developed at highly stressed portions of the crystal. These locally developed into very fine channel-like structures, mostly oriented sub-parallel to crystallographic planes. Most of the channels developed into slits and finally into fractures. Fracture walls migrated by solution transfer leading to changes in shape of the crystal fragments. The resulting polygonal deformation microstructure could easily be mistaken for a dynamically recrystallised `crystal plastic' microstructure. Therefore, care should be taken to use such optical microstructures as conclusive evidence for dislocation creep. This is important, because the occurrence of these microstructures is the strongest argument for dislocation creep in crustal rocks.
Keywords: CATACLASIS; MICROCRACKS; DEFORMATION; ULTRASTRUCTURE